Microstructural response and strain hardening in deep cold rolled nickel-based superalloy for aerospace application - Kumar, Dharmesh (2018)
Fatigue crack resistance is a critical factor for the performance of aero-engine components. Deep cold rolling (DCR) is one promising surface enhancement technique, as it generates deep compressive residual stresses with the good surface finish. In this work, the influence of DCR process on the microstructure and mechanical properties of nickel-based superalloy (Udimet 720Li) was investigated. After DCR process, a deep layer of compressive residual stress up to 1mm was observed, which agrees well with the depth profile of Vickers micro-hardness. Statistical analysis of Grain Orientation Spread (GOS) in the Electron Back Scattered Diffraction (EBSD) map also shows the presence of strain hardening layer after the DCR process. Results are discussed with a focus on the strengthening mechanism through grain refinement, the addition of Low Angle Grain Boundaries (LAGBs), and intragranular deformation in the sub-surface. Overall, this fundamental understanding could shed light on a new pathway to develop nickel-based superalloys with an excellent mechanical performance for aerospace applications.